The nature of nature why we need the wild - Sala, Enric (Washington, DC National Geographic, 2020)
The Nature of Nature explores how the natural world works, outlines the consequences of its unraveling by our activities, and offers practical solutions-with a description of societal and economic benefits. The first ten chapters of this book are a step-by-step crash course in ecology-you might call it "ecology for people in a hurry": what species do, how they co-exist, and how the natural world self-assembles and works, compared to our human-built environment-with ideas on how to run our society and economy more efficiently. Chapter 11 discusses the moral case for the conservation of life on Earth, because utility cannot be the only lens through which we see the world. In other words: Do other creatures have a right to exist, and why? And finally, Chapter 12 explains why it makes more economic sense to protect more of the natural world than to degrade it. By talking to the brain and the heart, and at the same time reaching into the pocket, this book illuminates an inner appreciation for all life on Earth, instills a greater sense of humility, and helps us understand why we need a world with wild places
Includes bibliographical references and index.
Keywords: Human ecology